Lithium iron phosphate positive electrode active material, positive electrode sheet and lithium ion battery
Patent Information
- Application Number
- JP2024547924
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-15
- Filing Date
- 2023-02-07
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2043-02-07
AI Technical Summary
【0079】 本開示の有益な効果を強調するために、以下の比較例を提供する。
Smart Images

Figure 2025506057000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This disclosure claims priority to Chinese Patent Application No. 202210139348.3, entitled "Lithium iron phosphate positive electrode active material, positive electrode sheet and lithium ion battery," filed on February 15, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to the field of lithium ion batteries, and in particular to lithium iron phosphate active cathode materials, cathode sheets and lithium ion batteries.
[0003] background Lithium iron phosphate materials are widely used due to their high safety, low cost, low environmental impact, and other advantages. However, lithium iron phosphate materials also have obvious defects. That is, due to the low compressed density of lithium iron phosphate materials, the energy density of batteries prepared with lithium iron phosphate materials is low, which cannot meet the demand for batteries with long battery life. In order to improve the energy density of batteries, lithium iron phosphate materials with high compressed density are needed. However, as the compressed density of lithium iron phosphate materials increases, the electrochemical performance of the batteries often decreases.
[0004] overview In a first aspect, the present disclosure provides a lithium iron phosphate active cathode material.
[0005] The lithium iron phosphate positive electrode active material includes a first lithium iron phosphate material and a second lithium iron phosphate material. When the cumulative volume distribution rate of the first lithium iron phosphate material is 50%, the corresponding particle size is D 1 v 50 μm. When the cumulative volume distribution rate of the second lithium iron phosphate material is 50%, the corresponding particle size is D 2 v 50μm. D 1 v 50 is in the range of 0.3 to 0.95, D 2 vD 50 is in the range of 1.0 to 3.5. When the cumulative volume distribution rate of the lithium iron phosphate positive electrode active material is 90%, 10%, and 50%, the corresponding particle size is D v 90μm, D v 10 μm, and D v 50 μm. When the cumulative particle distribution rate of the lithium iron phosphate positive electrode active material is 50%, the corresponding particle size is D n The particle size of the lithium iron phosphate positive electrode active material satisfies the following relationship: 0.16≦(D v 90-D v 10) / D v 50+D v 50×D n 50≦31.1.
[0006] In some embodiments of the present disclosure, the maximum compressed density is between 2.55 and 2.85 g / cm 3 It is.
[0007] In some embodiments of the present disclosure, the D of the first lithium iron phosphate material 1 v 50 is in the range of 0.4 to 0.85, and the D of the second lithium iron phosphate material 2 v 50 is in the range of 1.2 to 3.0.
[0008] In some embodiments of the present disclosure, (D v 90-D v 10) / D v 50+D v 50×D n 50 is in the range of 0.2 to 31.
[0009] In some embodiments of the present disclosure, D v 50×D n 50 is in the range of 0.05 to 4.9.
[0010] In some embodiments of the present disclosure, the D of the lithium iron phosphate positive electrode active material v 50 is in the range of 0.25 to 3.5.
[0011] In some embodiments of the present disclosure, the mixing weight ratio of the first lithium iron phosphate material to the second lithium iron phosphate material is in the range of 1:(1-9), and even in the range of 1:(1-4).
[0012] In some embodiments of the present disclosure, the first lithium iron phosphate material has a carbon coating layer on a surface thereof and / or the second lithium iron phosphate material has a carbon coating layer on a surface thereof.
[0013] In a second aspect, the present disclosure provides a positive electrode sheet comprising a lithium iron phosphate positive electrode active material according to the first aspect of the present disclosure.
[0014] In some embodiments of the present disclosure, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector. The positive electrode active material layer includes a lithium iron phosphate positive electrode active material, a binder, and a conductive agent.
[0015] In some embodiments of the present disclosure, the positive electrode active material layer is formed by coating a positive electrode paste, including lithium iron phosphate positive electrode active material, a conductive agent, a binder, and a solvent, onto a positive electrode current collector.
[0016] In a third aspect, the present disclosure provides a lithium-ion battery comprising a positive electrode sheet according to the second aspect of the present disclosure.
[0017] In some embodiments of the present disclosure, the lithium ion battery further includes a negative electrode sheet, an electrolyte, and a separator located between the positive and negative electrode sheets. [Brief description of the drawings]
[0018] [Figure 1] 1 shows cycle performance curves of each pouch battery in Embodiments 1 to 5 and Comparative Example 1 of the present disclosure.
[0019] Detailed Description The above description is some embodiments of the present disclosure. It should be noted that some modifications and variations may be made by those skilled in the art without departing from the principles of the present disclosure, which fall within the protection scope of the present disclosure.
[0020] The present disclosure provides a lithium iron phosphate positive electrode active material that has a high packed density, enabling batteries prepared therewith to have good electrochemical performance.
[0021] In a first aspect, the present disclosure provides a lithium iron phosphate active cathode material.
[0022] The lithium iron phosphate positive electrode active material includes a first lithium iron phosphate material and a second lithium iron phosphate material. When the cumulative volume distribution rate of the first lithium iron phosphate material is 50%, the corresponding particle size is D 1 v 50 μm. When the cumulative volume distribution rate of the second lithium iron phosphate material is 50%, the corresponding particle size is D 2 v 50μm. D 1 v 50 is in the range of 0.3 to 0.95, D 2 v D 50 is in the range of 1.0 to 3.5. When the cumulative volume distribution rate of the lithium iron phosphate positive electrode active material is 90%, 10%, and 50%, the corresponding particle size is D v 90μm, D v 10μm, D v 50 μm. When the cumulative particle distribution rate of the lithium iron phosphate positive electrode active material is 50%, the corresponding particle size is D n The particle size of the lithium iron phosphate positive electrode active material satisfies the following relationship: 0.16≦(D v 90-D v 10) / D v 50+D v 50×D n 50≦31.1.
[0023] In this disclosure, the positive electrode active material has a high compressed density (2.55 g / cm 3In order to ensure that the positive electrode active material has a particle size of 0.1 to 0.5 μm or more, two lithium iron phosphate materials with different particle sizes are used, and the particle size of the resulting positive electrode active material meets a specific relationship. This promotes the improvement of the energy density of the battery prepared using the positive electrode active material. Furthermore, the battery prepared using the positive electrode active material has excellent electrochemical performance, especially cycle performance.
[0024] In some embodiments of the present disclosure, the lithium iron phosphate positive electrode active material has a maximum pressed density of 2.55 g / cm 3 In some embodiments of the present disclosure, the maximum compressed density is 2.55 to 2.85 g / cm 3 It should be understood that the maximum pressed density of a particular material referred to in this disclosure refers to the maximum pressed density obtained by testing the material with a powder pressing density meter, or the maximum available pressed density of a positive electrode sheet prepared with this material. The maximum pressed density of a positive electrode sheet refers to the corresponding pressed density of the electrode sheet when the active material particles in the positive electrode sheet are crushed under a particular pressure.
[0025] First lithium iron phosphate material D 1 v 50 value and the D of the second lithium iron phosphate material 2 v The D50 value can be obtained from the respective laser particle size distribution diagram. Specifically, the test equipment is a laser particle size analyzer (such as Malvern 3000). The test method can be found in GB / T 19077-2016 / ISO 13320:2009 Particle size analysis - Laser diffraction method. When the cumulative volume distribution rate of the material is 50%, the corresponding particle size is called the median particle size of the material. Similarly, the particle size D of the lithium iron phosphate positive electrode active material is n 50, D v 90, D v 10, and D v The value of 50 can be obtained by determining the laser particle size distribution of a mixed powder obtained by mixing the first lithium iron phosphate material and the second lithium iron phosphate material.
[0026] In this disclosure, D 1v 50 <D 2 v 50. The D of lithium iron phosphate material 1 v When D is small, the lithium ion diffusion path is relatively short, and the prepared battery has good electrical performance. 2 v When the particle size D 50 is large, the compression density of the positive electrode active material can be increased. v 50 within the above range ensures that the two lithium iron phosphate materials can be formed into a dense mass, thus improving the packed density of the resulting positive electrode active material without compromising the cycling performance of the battery.
[0027] In some embodiments of the present disclosure, the D of the first lithium iron phosphate material 1 v 50 is in the range of 0.4 to 0.85, and the D of the second lithium iron phosphate material 2 v 50 is in the range of 1.2 to 3.0. In this case, the use of a positive electrode active material obtained by mixing two lithium iron phosphate materials can satisfactorily ensure the high compression density of the positive electrode sheet and the good electrochemical performance of the battery.
[0028] In some embodiments of the present disclosure, (D v 90-D v 10) / D v 50+D v 50×D n 50 is in the range of 0.2 to 31. In some embodiments, (D v 90-D v 10) / D v 50+D v 50×D n 50 is in the range of 0.5 to 30.
[0029] In some embodiments of the present disclosure, D v 50×D nIn this case, the positive electrode active material has a high compressed density and excellent electrochemical performance. v 50×D n D50 may be in the range of 0.1 to 4.5. v 50×D n 50 can be in the range of 0.6 to 4.
[0030] In some embodiments of the present disclosure, the D of the lithium iron phosphate positive electrode active material v 50 is in the range of 0.25 to 3.5. D v D 50 represents the particle size corresponding to the cumulative volume distribution rate of the positive electrode active material being 50%. v When the .50 value is within the above range, it is guaranteed that the positive electrode active material particles are properly laminated, the polarization strength of the electrode sheet is low, the lithium ion permeation rate during the battery cycle process is fast, and the energy density of the secondary battery is high.
[0031] In the present disclosure, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is not particularly limited as long as it is ensured that the particle size of the positive electrode active material formed by mixing the two meets the above-mentioned relational formula. In some embodiments of the present disclosure, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1:(1-9), or even in the range of 1:(1-4). In this case, the positive electrode active material formed by mixing the two lithium iron phosphate materials can satisfactorily ensure a high compression density of the electrode sheet and good cycle performance of the battery.
[0032] In some embodiments of the present disclosure, the first lithium iron phosphate material has a carbon coating layer on its surface, and / or the second lithium iron phosphate material has a carbon coating layer on its surface. The carbon coating layer can be obtained by sequentially sanding, spray drying, and sintering a mixed slurry of a phosphorus source, an iron source, a lithium source, and a carbon source. In the present disclosure, the specific preparation method of the two lithium iron phosphate materials is not limited. Due to the presence of the carbon coating layer, the first and second lithium iron phosphate materials can have good electrical conductivity and reduce side reactions with the electrolyte. The positive electrode active material obtained by mixing the two has good electrical conductivity and good cycle performance of the battery.
[0033] According to the lithium iron phosphate positive electrode active material provided in the first aspect of the present disclosure, by mixing two lithium iron phosphate materials that meet the requirements of specific particle size parameters, it is possible to ensure that the resulting positive electrode active material has a high compaction density, and that the battery prepared using the positive electrode active material has good cycle performance and rate performance. The preparation method is suitable for use in large-scale production because the process is simple and easy to operate.
[0034] In a second aspect, the present disclosure provides a positive electrode sheet comprising a lithium iron phosphate positive electrode active material according to the first aspect of the present disclosure.
[0035] In some embodiments of the present disclosure, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector. The positive electrode active material layer includes a lithium iron phosphate positive electrode active material, a binder, and a conductive agent.
[0036] The maximum compression density of the positive electrode sheet is 2.55 g / cm 3 In some embodiments, the maximum compressed density is 2.55 to 2.85 g / cm 3 It is.
[0037] In some embodiments of the present disclosure, the positive electrode active material layer is formed by coating a positive electrode paste including a lithium iron phosphate positive electrode active material, a conductive agent, a binder, and a solvent on a positive electrode current collector. The solvent can be one or more of N-methylpyrrolidone (NMP), acetone, and dimethylacetamide (DMAC). The positive electrode current collector includes any one of aluminum foil, carbon-coated aluminum foil, and perforated aluminum foil. The conductive agent includes, but is not limited to, one or more of carbon nanotubes, graphene carbon black, carbon fiber, and the like. The binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylate, polyacrylonitrile (PAN), sodium carboxymethyl cellulose (CMC), and sodium alginate.
[0038] In a third aspect, the present disclosure provides a lithium-ion battery comprising a positive electrode sheet according to the second aspect of the present disclosure.
[0039] In some embodiments of the present disclosure, the lithium ion battery further includes a negative electrode sheet, an electrolyte, and a separator located between the positive and negative electrode sheets.
[0040] Lithium-ion batteries that use positive electrode sheets have high energy density and excellent cycle performance.
[0041] In the following, the technical solutions of the present disclosure will be described in combination with specific embodiments. EXAMPLES
[0042] Example 1
[0043] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0044] When the first lithium iron phosphate material LFP-1 was used and the cumulative volume distribution rate was 50%, the corresponding particle size determined was 0.56 μm, i.e. D 1 v 50 was 0.56.
[0045] When the second lithium iron phosphate material LFP-2 was used and the cumulative volume distribution rate was 50%, the corresponding particle size determined was 1.85 μm, i.e. D 2 v 50 was 1.85.
[0046] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 2:8 to obtain the lithium iron phosphate cathode active material LFP-3. When the cumulative volume distribution rate of the LFP-3 material was 10%, 50%, and 90%, the corresponding particle sizes were 0.31 μm, 0.74 μm, and 4.97 μm, respectively (i.e., D v 10 is 0.31, D v 50 is 0.74, D v When the cumulative number distribution rate is 50%, the corresponding particle size is 0.84 μm (i.e., D n 50 was 0.84). The calculation gives (D v 90-D v 10) / D v 50+D v 50×D n 50=6.92, and D v 50×D n 50=0.6216.
[0047] The positive electrode active material LFP-3 was prepared into a positive electrode sheet by mixing the LFP-3 material with a binder (specifically, polyvinylidene fluoride (PVDF)) and conductive carbon black in a weight ratio of 85:5:10, adding an appropriate amount of N-methylpyrrolidone (NMP), and mixing uniformly to obtain a positive electrode paste. The positive electrode paste was coated on both sides of a carbon-coated aluminum foil and dried to obtain a positive electrode sheet. The maximum compressed density of the positive electrode sheet without particle fracture was determined. The maximum compressed density of the positive electrode sheet was 2.63 g / cm. 3 It was determined that.
[0048] Preparation of pouch lithium ion battery: A positive electrode sheet prepared with the positive electrode active material LFP-3 of Example 1 was used as the positive electrode. A graphite electrode sheet was used as the negative electrode. A polypropylene film was used as the separator. As the electrolyte, a solution containing 1.0 mol / L of LiPF6 in ethylene carbonate (EC): dimethyl carbonate (DMC) = 1: 1 (volume ratio) was used. After assembly, a pouch battery was obtained.
[0049] Example 2
[0050] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0051] The first lithium iron phosphate material LFP-1 was used, 1 v 50 (the concept is as described in Example 1 and will not be repeated hereafter) was determined to be 0.65.
[0052] Using the second lithium iron phosphate material LFP-2, 2 v 50 (the concept is as described in Example 1 and will not be repeated hereafter) was determined to be 2.5.
[0053] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7 to obtain the lithium iron phosphate positive electrode active material LFP-3. v 10 is 0.19, and D v 50 is 1.15, D v 90 is 4.97, D n 50 is 1.89, (D v 90-D v 10) / D v 50+D v 50×D n 50=6.33, D v 50×D n 50=2.1735.
[0054] The positive electrode active material LFP-3 obtained in Example 2 was prepared into a positive electrode sheet and assembled into a pouch battery according to the method described in Example 1. The maximum compressed density of the positive electrode sheet in Example 2 was 2.67 g / cm 3 It was determined that.
[0055] Example 3
[0056] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0057] The first lithium iron phosphate material LFP-1 was used, 1 v 50 was determined to be 0.92.
[0058] Using the second lithium iron phosphate material LFP-2, 2 v 50 was determined to be 3.43.
[0059] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 4:6 to obtain the lithium iron phosphate positive electrode active material LFP-3. v 10 is 0.31, D v 50 is 0.89, and D v 90 is 6.67, D n 50 is 4.31, (D v 90-D v 10) / D v 50+D v 50×D n 50=10.98, D v 50×D n 50=3.8359.
[0060] The positive electrode active material LFP-3 obtained in Example 3 was prepared into a positive electrode sheet and assembled into a pouch battery according to the method described in Example 1. The maximum compressed density of the positive electrode sheet of Example 3 was 2.60 g / cm 3 It was determined that.
[0061] Example 4
[0062] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0063] The first lithium iron phosphate material LFP-1 was used, 1 v 50 was determined to be 0.15.
[0064] Using the second lithium iron phosphate material LFP-2, 2 v 50 was determined to be 1.15.
[0065] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7 to obtain the lithium iron phosphate positive electrode active material LFP-3. v 10 is 0.17, and D v 50 is 0.25, D v 90 is 6.7, D n 50 is 2.77, (D v 90-D v 10) / D v 50+D v 50×D n 50=26.81, D v 50×D n 50=0.6925.
[0066] The positive electrode active material LFP-3 obtained in Example 4 was prepared into a positive electrode sheet and assembled into a pouch battery according to the method described in Example 1. The maximum compressed density of the positive electrode sheet in Example 4 was 2.79 g / cm 3 It was determined that.
[0067] Example 5
[0068] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0069] The first lithium iron phosphate material LFP-1 was used, 1 v 50 was determined to be 0.92.
[0070] Using the second lithium iron phosphate material LFP-2, 2 v 50 was determined to be 1.23.
[0071] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 1:9 to obtain the lithium iron phosphate positive electrode active material LFP-3. v 10 is 0.25, D v 50 is 0.67, and D v 90 is 5.79, D n 50 is 1.32, (D v 90-D v 10) / D v 50+D v 50×D n 50=9.15, D v 50×D n 50=0.8844.
[0072] The positive electrode active material LFP-3 obtained in Example 5 was prepared into a positive electrode sheet and assembled into a pouch battery according to the method described in Example 1. The maximum compressed density of the positive electrode sheet of Example 5 was 2.83 g / cm 3 It was determined that.
[0073] Example 6
[0074] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0075] The first lithium iron phosphate material LFP-1 was used, 1 v 50 was determined to be 0.90.
[0076] Using the second lithium iron phosphate material LFP-2, 2 v 50 was determined to be 1.12.
[0077] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 1:9 to obtain the lithium iron phosphate positive electrode active material LFP-3. v 10 is 0.8, Dv 50 is 3.5, D v 90 is 4.23, D n 50 is 0.23, (D v 90-D v 10) / D v 50+D v 50×D n 50=1.785, D v 50×D n 50=0.805.
[0078] The positive electrode active material LFP-3 obtained in Example 6 was prepared into a positive electrode sheet and assembled into a pouch battery according to the method described in Example 1. The maximum compressed density of the positive electrode sheet of Example 6 was 2.62 g / cm 3 It was determined that.
[0079] To highlight the beneficial effects of the present disclosure, the following comparative examples are provided.
[0080] Comparative Example 1
[0081] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0082] The first lithium iron phosphate material LFP-1 was used, 1 v 50 was determined to be 0.95.
[0083] Using the second lithium iron phosphate material LFP-2, 2 v 50 was determined to be 3.45.
[0084] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 1:9 to obtain the lithium iron phosphate positive electrode active material LFP-3. v 10 is 0.94, D v 50 is 4.55, D v 90 is 7.89, D n 50 is 6.78, (D v 90-D v 10) / D v50+D v 50×D n 50=32.38, which was outside the range of 0.16 to 31.1 defined in this disclosure.
[0085] According to the method described in Example 1, the positive electrode active material LFP-3 obtained in Comparative Example 1 was prepared into a positive electrode sheet and assembled into a pouch battery. The maximum compressed density of the positive electrode sheet of Comparative Example 1 was 2.49 g / cm 3 It was determined that.
[0086] Comparative Example 2
[0087] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0088] The first lithium iron phosphate material LFP-1 was used, 1 v 50 was determined to be 1.24, which was outside the range of 0.3 to 0.95 defined in this disclosure.
[0089] Using the second lithium iron phosphate material LFP-2, 2 v 50 was determined to be 4.2, which was outside the range of 1.0 to 3.5 defined in this disclosure.
[0090] The LFP-1 and LFP-2 materials were mixed in a specific weight ratio to obtain the lithium iron phosphate cathode active material LFP-3. v 10 is 0.87, D v 50 is 3.21, D v 90 is 8.32, D n 50 is 3.65, (D v 90-D v 10) / D v 50+D v 50×D n 50=14.04.
[0091] According to the method described in Example 1, the positive electrode active material LFP-3 obtained in Comparative Example 2 was prepared into a positive electrode sheet and assembled into a pouch battery. The maximum compressed density of the positive electrode sheet of Comparative Example 2 was 2.35 g / cm 3 It was determined that.
[0092] To strongly support the beneficial effects of the present disclosure, the pouch cells of each of the examples and comparative examples were tested for the following electrochemical performance.
[0093] 1) Cycle performance: Each pouch battery was subjected to a charge-discharge cycle test at 25°C and 0.5C / 0.5C. The voltage range was 2.0-3.8V. During charging, the battery was charged at a constant current of 0.5C up to 3.8V, and then charged at a constant voltage up to a cut-off current of 0.05C. The coulombic efficiency of the first cycle and the capacity retention rate after 1000 charge-discharge cycles were tested.
[0094] 2) Discharge capacity per gram of positive electrode active material: In the voltage range of 2.0 to 3.8 V, the positive electrode active material LFP-3 of each Example and Comparative Example was charged to 3.8 V at a constant current LFP-3 of 0.1 C, and then at a constant voltage to a cutoff current of 0.05 C. The positive electrode active material was then discharged to 2.0 V at a constant current of 0.1 C. The charge-discharge process was repeated three times. The third discharge capacity was recorded as C0, and C0 divided by the weight of LFP-3 in each Example and Comparative Example was the capacity per gram of LFP-3.
[0095] 1 shows cycle performance curves of each pouch battery in Embodiments 1 to 5 and Comparative Example 1. The coulombic efficiency of the first cycle, the capacity retention rate after 1000 cycles, and other data of the batteries in each Example and Comparative Example are summarized in Table 1 below. [Table 1]
[0096] As can be seen from FIG. 1 and Table 1, the positive electrode active material prepared by the method provided in the present disclosure has a higher packed density, and the battery prepared thereby has excellent electrochemical performance. For example, the first cycle coulombic efficiency can be over 96%, the positive electrode has a high capacity per gram, and the capacity retention rate after 1000 cycles is still over 90%. In contrast, the particle size relationship of the positive electrode active material of Comparative Example 1 is outside the range specified in the present disclosure. As a result, the packed density of the positive electrode sheet is 2.5 g / cm 3 , but is still lower than the compressed density of the positive electrode in the present disclosure. In addition, the battery of Comparative Example 1 has low coulombic efficiency and cycle performance in the first cycle, which is far inferior to the battery of the present disclosure. In Comparative Example 2, the particle size relationship of the positive electrode active material is within the range specified in the present disclosure, but the median particle size of the two raw materials forming the positive electrode active material is not within the range required by the present disclosure. Therefore, the compressed density of the positive electrode sheet is low, and the cycle performance of the battery is poor.
[0097] The above embodiments show only some implementation forms of the present disclosure and are described in detail, but this should not be interpreted as limiting the scope of the present disclosure. It should be understood that some variations and improvements may be made by those skilled in the art without departing from the spirit of the present disclosure, and all of them are contemplated within the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure shall be defined by the appended claims.
Claims
1. A lithium iron phosphate positive electrode active material, A first lithium iron phosphate material and a second lithium iron phosphate material, and when the cumulative volume distribution rate of the first lithium iron phosphate material is 50%, the corresponding particle size is D 1 v 50 μm, and the cumulative volume distribution rate of the second lithium iron phosphate material is 50%, the corresponding particle size is D 2 v 50 μm, D 1 v 50 is within the range of 0.3 to 0.95, and D 2 v 50 is within the range of 1.0 to 3.5, When the cumulative volume distribution rate of the lithium iron phosphate positive electrode active material is 90%, 10%, and 50%, the corresponding particle size is D v 90μm, D v 10 μm, and D v 50 μm, and the cumulative particle number distribution rate of the lithium iron phosphate positive electrode active material is 50%, the corresponding particle size is D n 50 μm, and the particle size of the lithium iron phosphate positive electrode active material satisfies the following relationship: 0.16≦(D v 90-D v 10) / D v 50+D v 50×D n 50≦31.1 Lithium iron phosphate positive electrode active material.
2. The maximum compressed density of the lithium iron phosphate positive electrode active material is 2.55 to 2.85 g / cm 3 The lithium iron phosphate positive electrode active material according to claim 1 , wherein the content of the lithium iron phosphate in the positive electrode active material is within the range of
3. D of the first lithium iron phosphate material 1 v 50 is in the range of 0.4 to 0.85, and the D of the second lithium iron phosphate material 2 v 3. The lithium iron phosphate positive electrode active material according to claim 1, wherein 50 is in the range of 1.2 to 3.
0.
4. (D v 90-D v 10) / D v 50+D v 50 x D n 50 is in the range of 0.2 to 31. The lithium iron phosphate positive electrode active material according to any one of claims 1 to 3.
5. D v 50 x D n The lithium iron phosphate positive electrode active material according to any one of claims 1 to 4, wherein 50 is in the range of 0.05 to 4.
9.
6. D v The lithium iron phosphate positive electrode active material according to any one of claims 1 to 5, wherein 50 is in the range of 0.25 to 3.
5.
7. The weight ratio of the first lithium iron phosphate material to the second lithium iron phosphate material is in the range of 1: (1 to 9). The lithium iron phosphate positive electrode active material according to any one of claims 1 to 6.
8. The lithium iron phosphate positive electrode active material according to any one of claims 1 to 7, wherein the first lithium iron phosphate material has a carbon coating layer on a surface thereof, and / or the second lithium iron phosphate material has a carbon coating layer on a surface thereof.
9. A positive electrode sheet comprising the lithium iron phosphate positive electrode active material according to any one of claims 1 to 8.
10. 10. The positive electrode sheet according to claim 9, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector, the positive electrode active material layer including the lithium iron phosphate positive electrode active material, a binder, and a conductive agent.
11. The positive electrode sheet according to claim 10, wherein the positive electrode active material layer is formed by coating a positive electrode paste containing the lithium iron phosphate positive electrode active material, the conductive agent, the binder and a solvent on the positive electrode current collector.
12. A lithium ion battery comprising the positive electrode sheet according to any one of claims 9 to 11.
13. 13. The lithium ion battery of claim 12, further comprising a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet.
Citation Information
Patent Citations
Positive electrode material lithium iron phosphate and preparation method thereof
CN109665508A
Positive pole active material, positive pole piece and electrochemical energy storage device
CN110233259A
High-compaction low-temperature lithium iron phosphate material, lithium battery positive plate and preparation method thereof
CN113086959A
Lithium iron phosphate positive electrode material as well as preparation method and application thereof
CN113800493A